The Impact of Modernization on Social and Cultural Values: A Basic Social and Cultural Sciences Review - Angkasawati, Angkasawati (Cita konsultindo, 2024)
Modernization has profoundly influenced social and cultural values across the globe, shaping societies in ways that often challenge traditional norms and practices. This article examines the impact of modernization on social structures, cultural identity, and community relationships, with a focus on the fundamental theories of social and cultural sciences. It explores how technological advancements, urbanization, and globalization contribute to shifts in values such as individualism, materialism, and social cohesion. By analyzing case studies and existing literature, the study evaluates the consequences of these changes on various aspects of life, including family dynamics, community engagement, and cultural heritage. The findings highlight the need for critical reflection on the effects of modernization, advocating for the preservation of cultural identity while embracing beneficial aspects of modernity. Ultimately, this article aims to provide insights into the complexities of modernization and its implications for social and cultural values.